Assessment of Sleep Disorders Among School Children - Vidhya Shankari N (Asian Journal of Medical Research, 2021)
Background: The aim is to assess sleep disorders among school children. Subjects and Methods: One hundred eighty school going children in age ranged 5-16 years of either gender who were found to have any kind of sleep disorders were included. Various sleep disorders such as insomnias, parasomnias, organic sleep disorders and day time symptoms etc. was recorded. Results: Age group 5-8 years had 25 boys and 30 girls, 9-12 years had 30 boys and 26 girls, 13- 16 years had 25 boys and 44 girls. A significant difference was observed (P <0.05). Environmental and stress factors comprised of regular waking time in 17% sometimes and 83% often, regular bed time seen in 25% sometimes and 75% often, watching TV late night in 35% sometimes and 65% often, TV set in room in 32% sometimes and 68% often, noise in 14% sometimes and 86% often, light in 18% sometimes and 40% often, household smoking in 30% sometimes and 50% often, allergy in 50% sometimes and 20% often, infection in 45% sometimes and 35% often and family disturbances in 24% sometimes and 26% often and chronic illness in 2% sometimes and 7% often. A significant difference was observed (P <0.05). Conclusion : Most common sleep disorder observed was insomnias, parasomnias, organic sleep disorders and day time symptoms. Environmental and stress factors such as watching TV late night, TV set in room, noise, light, household smoking, allergy, infection, family disturbances and chronic illness play an important role.